Visualization of the Nyadap Kawung Process in the Hideung Geulis Theater Performance in the Banceuy Traditional Village, Subang - Cahyani, Sinta Rizki; Pujiono, Bagong; Dayari, Achmad (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
Banceuy Subang Traditional Village is a traditional village that still maintains traditional values passed down from ancestors such as the tradition of the kawung nyadap process or commonly known as sugar palm tapping. In Banceuy, there are still some people who tap kawung trees to take field water and process it into palm sugar. Each process of tapping a kawung tree has an interesting meaning that can be visualized through a theatrical performance. To organize the formation of the visualization of the nyadap kawung process, it is supported by Gustav Freytag's dramatic structure theory which includes five elements, namely exposition, complication, climax, reversal, deoument. This research uses a qualitative approach. In research, a qualitative approach can be taken through observation, interviews and literature studies. The results of this research present a visualization of the process of tapping kawung into theater characters, there are three main figures visualized, namely 1. Hideung Geulis as a kawung tree, 2. Asep as a tapper of kawung trees and 3. Traditional Leader as an elder who perform the nyadap kawung ritual.